2010
DOI: 10.1002/esp.1938
|View full text |Cite
|
Sign up to set email alerts
|

Towards a protocol for laser scanning of rock surfaces

Abstract: The precision of height measurements derived from laser scanning a weathered rock surface was analysed. Different registration methods for comparing surfaces to deduce weathering were assessed and the most precise was found to be the method that used registration shapes as control, located in different planes relative to the scanned surface. In addition, the different sources of error in scanning precision were assessed by varying factors such as scan distance, lens confi guration, scan angle and the nature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 15 publications
(15 reference statements)
0
13
0
Order By: Relevance
“…Over the last decade, terrestrial laser scanners proved capable of generating very high quality DEM data (e.g. Heritage and Hetherington, 2007;Alho et al, 2009;Hodge et al, 2009a,b;Schaefer and Inkpen, 2010) and have almost become routine in some DEM collection strategies. However, they remain relatively expensive items of technology and have only recently become truly portable.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, terrestrial laser scanners proved capable of generating very high quality DEM data (e.g. Heritage and Hetherington, 2007;Alho et al, 2009;Hodge et al, 2009a,b;Schaefer and Inkpen, 2010) and have almost become routine in some DEM collection strategies. However, they remain relatively expensive items of technology and have only recently become truly portable.…”
Section: Introductionmentioning
confidence: 99%
“…Casas et al, 2012;Passalacqua et al, 2012;Grove et al, 2013;Sofia et al, 2014a). Heritage and Hetherington, 2007;Schaefer and Inkpen, 2010). Aside from airborne laser scanning (ALS), among the high-resolution survey techniques, terrestrial laser scanning (TLS) has demonstrated to be capable of generating very high-resolution digital terrain models (DEMs) (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring and monitoring surfaces and objects in three dimensions (3D) is critical to many studies in the Earth sciences. Methods for generating a digital elevation model (DEM) of a surface or a 3D scan of an object include airborne (Allouis et al ., ) and terrestrial (Hodge et al ., ) time‐of‐flight light detection and ranging (LiDAR), laser scanning (Lane et al ., ; Smart et al ., ; Schaefer and Inkpen, ), interferometric synthetic aperture radar (InSAR/IfSAR) (Milledge et al ., ), white light interferometry (Candela et al ., ), photogrammetry (Lane, , Lane et al ., ; Baily et al ., ; Brasington and Smart, ), GPS surveys (Chassereau et al ., ), total station surveys (Hubbard and Hubbard, ), and stake placement (Furbish, ). The Microsoft® Kinect™, a ~ US $100 input device for the Xbox 360® video game system, is capable of providing high spatial ( x , y ) resolution (~2–20 mm) and high distance ( z ) resolution (1–75 mm) 3D data.…”
Section: Introductionmentioning
confidence: 99%